Birth preparedness and complication readiness among primigravida women attending tertiary care hospital in a rural area - Patil, Monika S.; Vedpathak, Vinod L.; Aswar, Nandkeshav R.; Deo, Deepali S.; Dahire, Prashant L. (International Journal Of Community Medicine And Public Health, 2017)
Background: Maternal mortality in developing countries is still alarming. Each pregnancy may face the risk of sudden, unpredictable complications. Birth preparedness and complication readiness (BPACR) is a strategy that encourages pregnant women and their families to effectively plan for deliveries and deal with emergencies. An objective of study was to assess the status of BPACR among primigravida women and factors affecting the status of BPACR. Methods: A Cross sectional study was conducted among 400 primigravida women attending ANC OPD at tertiary care hospital, from August-November 2015. Data was collected by interviewing the subjects using pre-tested, pre-designed structured questionnaire. BPACR index was calculated. Results: In this study BPACR index was 55.83%. Most of women (98.14%) identified skilled birth attendant for delivery. Though acceptable levels of registration of women in first trimester (79.75%) and identification of modes of transport in emergency (72.25%), TT2 coverage was very low (77.75%). About 63% women were aware about transportation provided by government & 70.25% women were aware about importance of 4 or more ANC visits during pregnancy. But only 68.50% women were aware about consumption of 100-FSFA tablets, whereas 31.50% of women had saved money to pay for expenses. Very few (29.75%) women identified compatible blood donors. 40.75% women knew about any one danger signs of pregnancy. Overall no women knew about all 8 danger signs of pregnancy. Conclusions: Age and education of women and of their husbands plays an important role in awareness regarding components of BPACR.